Pengaruh Iklan Shopee Big Sale di Youtube dan Promosi Penjualan Terhadap Minat Beli Para Pengguna Shopee di DKI Jakarta - Adellia Jati Pangestika; Harry Sardjono (UNIVERSITAS KALBIS, 2022)
This study aims to determine how much influence advertising and sales promotions have on buying interest of Shopee users in DKI Jakarta. This research is a quantitative study using the SPSS Statistics 25 program with a total sample of 120 respondents who live in the DKI Jakarta area who know and use the Shopee application using nonprobability sampling and purposive sampling techniques. The results of this study indicate that advertising and sales promotions affect buying interest. The benefits of this research for Shopee companies are as input or evaluation materials to continue to improve and develop advertising and sales promotions so that Shopee can compete with other competitors.